Gas flaring reduction in nigeria in context of carbon dioxide (CO₂) reduction and utilisation requirements. - Abu, Robin Nyemenim (Cranfield University, 2021)
The growing demand for energy due to a rise in global population and an improved standard of living has resulted in the production, refining and consumption of hydrocarbon fuel. A consequence of this has been an increase in the global rate of natural gas flaring. While natural gas flaring is accepted as a waste of energy and natural resources, as well as a contravention of Nigeria’s current energy policy for sustainable development through natural gas conservation, natural gas flaring is still considered the most cost efficient and effective Associated Natural Gas (ANG) flaring management option in developing countries such as Nigeria. The need to further consolidate routine gas flaring reduction or management techniques has never been greater with the 2030 zero routine flaring initiative by the World Bank fast approaching. While there are several studies on natural gas utilisation techniques, they rarely consider the shortage of practical tools that integrate economic, technical, and regulatory factors into a gas flaring management framework; and also, the intricacies of the existing tools, which often comes at the expense of simplicity, to obtain real-time information output. Thus, the aim of this study was to develop a systematic framework and ANG management tool to aid the reduction of routine natural gas flaring in Nigeria. This research developed a systematic management framework (using a flowchart decision tree technique) and models to further develop a simple, relatively quick, flexible, and user-friendly ANG flaring management tool (using a MATLAB graphical user interface). This was integrated with techno-economic models for the Liquefied Natural Gas, Gas to Methanol and Gas to Wire ANG utilisation options using the ASPEN HYSYS computer software. The tool was then tested with data obtained from three fields A, B and C in the Niger Delta region of Nigeria. Field A is an offshore field in Bayelsa State in the South-West Niger Delta. Field B is an offshore field in Rivers State in the South-South Niger Delta while Field C is an onshore field in Delta State in the South-West Niger Delta. Results obtained showed the choice of Gas to Methanol option as the most optimal for Field A due to its preference for large gas volumes and cost effectiveness, Liquefied Natural Gas for Field B because of its proximity to the Liquefied Natural Gas pipeline infrastructure and Gas to Wire utilisation option for Field C due to its proximity to the electrical grid and high electricity requirements of that area when both economic and technical considerations were taken into account. The addition of further regional profiles within West Africa, as well as the consideration of more ANG utilisation options were among suggested areas for further research.
Keywords: Associated natural gas (ANG); gas flaring; gas flaring reduction; ANG utilisation options; ANG flaring management; hydrocarbon fuel